Weight gain among treatment‐naïve persons with HIV starting integrase inhibitors compared to non‐nucleoside reverse transcriptase inhibitors or protease inhibitors in a large observational cohort in the United States and Canada - Bourgi, Kassem; Jenkins, Cathy A; Rebeiro, Peter F; Palella, Frank; Moore, Richard D; Altoff, Keri N; Gill, John; Rabkin, Charles S; Gange, Stephen J; Horberg, Michael A; Margolick, Joseph; Li, Jun; et al. (Journal of the International AIDS Society, 2020)
Introduction Weight gain following antiretroviral therapy (ART) initiation is common, potentially predisposing some persons with HIV (PWH) to cardio‐metabolic disease. We assessed relationships between ART drug class and weight change among treatment‐naïve PWH initiating ART in the North American AIDS Cohort Collaboration on Research and Design (NA‐ACCORD). Methods Adult, treatment‐naïve PWH in NA‐ACCORD initiating integrase strand transfer inhibitor (INSTI), protease inhibitor (PI) or non‐nucleoside reverse‐transcriptase inhibitor (NNRTI)‐based ART on/after 1 January 2007 were followed through 31 December 2016. Multivariate linear mixed effects models estimated weight up to five years after ART initiation, adjusting for age, sex, race, cohort site, HIV acquisition mode, treatment year, and baseline weight, plasma HIV‐1 RNA level and CD4+ cell count. Due to shorter follow‐up for PWH receiving newer INSTI drugs, weights for specific INSTIs were estimated at two years. Secondary analyses using logistic regression and all covariates from primary analyses assessed factors associated with >10% weight gain at two and five years. Results Among 22,972 participants, 87% were male, and 41% were white. 49% started NNRTI‐, 31% started PI‐ and 20% started INSTI‐based regimens (1624 raltegravir (RAL), 2085 elvitegravir (EVG) and 929 dolutegravir (DTG)). PWH starting INSTI‐based regimens had mean estimated five‐year weight change of +5.9kg, compared to +3.7kg for NNRTI and +5.5kg for PI. Among PWH starting INSTI drugs, mean estimated two‐year weight change was +7.2kg for DTG, +5.8kg for RAL and +4.1kg for EVG. Women, persons with lower baseline CD4+ cell counts, and those initiating INSTI‐based regimens had higher odds of >10% body weight increase at two years (adjusted odds ratio = 1.37, 95% confidence interval: 1.20 to 1.56 vs. NNRTI). Conclusions PWH initiating INSTI‐based regimens gained, on average, more weight compared to NNRTI‐based regimens. This phenomenon may reflect heterogeneous effects of ART agents on body weight regulation that require further exploration.